Hippo signaling pathway in polycystic ovary syndrome - Wen, Jiahui; Cheng, Guan; Zhang, Yan; Liu, Su (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is a complex endocrine-metabolic disorder syndrome, that predominantly affects women of reproductive age. It is characterized by marked clinical heterogeneity involving multiple systems including reproductive, metabolic and immune systems, while existing diagnostic protocols remain inadequate for clinical needs. Moreover, the incomplete understanding of PCOS etiology has limited therapeutic strategies for symptomatic management rather than interventions targeting core pathological mechanisms, resulting in PCOS frequently persisting as a chronic condition with an increased risk of long-term complications such as type 2 diabetes, metabolic disorder-associated fatty liver disease and cardiovascular disease. This clinical reality underscores the urgent need to elucidate its pathogenic network at the molecular level. Emerging evidence suggests that the Hippo signaling pathway plays a central role in the pathological process of PCOS through dynamically regulating cell proliferation-apoptosis balance, differentiation programs and metabolic homeostasis. This review examines the molecular mechanisms governing Hippo signaling transduction and its physiological relevance, with a focused analysis of its diverse implications in PCOS pathophysiology, particularly in reproductive dysfunction, metabolic-endocrine disturbances, and immune dysregulation. These mechanistic insights not only advance our understanding of PCOS pathogenesis but also provide a theoretical foundation for developing signaling pathway-targeted precision therapies.